2023
DOI: 10.3390/polym15112531
|View full text |Cite
|
Sign up to set email alerts
|

Multi Scale Analysis of the Retting and Process Effect on the Properties of Flax Bio-Based Composites

Abstract: This research aimed to evaluate, at different scales (technical flax fiber, fiber band and flax composites, bio-based composites), the effect of retting and processing parameters on the biochemical, microstructural, and mechanical properties of flax-epoxy bio-based materials. On the technical flax fiber scale, a biochemical alteration of the fiber was observed as the retting increased (a decrease of the soluble fraction from 10.4 ± 0.2 to 4.5 ± 1.2% and an increase of the holocellulose fractions). This finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…The synchrotron and neutrons irradiation were used to detect the formation and changes in the hydrogen bonding, molecular and crystal structure of hemp fibres. It was observed that the hemp sample efficiently diffracted the synchrotron X-rays and neutrons up to 1 Å resolution [94], [95]. The sustainability and biodegradability of hemp materials have further supported the interacting capability of these materials with synchrotron X-rays and neutron radiations [96]- [98].…”
Section: Synchrotron X-rays and Neutrons Scattering Applicationsmentioning
confidence: 94%
“…The synchrotron and neutrons irradiation were used to detect the formation and changes in the hydrogen bonding, molecular and crystal structure of hemp fibres. It was observed that the hemp sample efficiently diffracted the synchrotron X-rays and neutrons up to 1 Å resolution [94], [95]. The sustainability and biodegradability of hemp materials have further supported the interacting capability of these materials with synchrotron X-rays and neutron radiations [96]- [98].…”
Section: Synchrotron X-rays and Neutrons Scattering Applicationsmentioning
confidence: 94%